Elementos para una actualización de la agenda campesina de la región de Manabí - Buendía, Fernando (2010)
The dominant visions of capitalist modernity have been identified with rurality backwardness, with agricultural and extractive activities grouped in the so-called industry primary of the economy and the presence of non-scientific and archaic ideologies. The spirit of progress, immersed in the maelstrom of capitalist domination, under the assumption that nature is endless, for several centuries and with increasing intensity, have been subjected to so-called "natural resources" in a process of over-exploitation unsustainable, so that has become the planet to the brink of environmental catastrophe. Imbued with the same fanaticism, Western civilization work, eager to model societies in his image and likeness, in long and bloody days of submission, It destructured, persecuted and dissolved most of the social events, cultural and policies of agrarian societies, even the native peoples of the West (fits highlight historic milestones as the colonization of the continents of the southern hemisphere, the inquisition, holy wars, the conquest of the western United States, the new "holy wars" Islamic peoples against Afghanistan, Iraq, Palestine, etc.) The current moment that passes humanity, characterized by the extension and intensification of global corporate capitalism, which shaped desconstituye accelerated and weakens states, societies and economies of the countries of the periphery, exacerbates the over exploitation of raw materials and natural resources to the extent that these are becoming scarce producing the growth of their prices to levels Historic. Spurred by the general tendency of capitalist profit system and decreasing the result of the narrowing of the market (which originated in the extreme polarization the distribution of wealth), multinational corporations adopt neoclassical forms of extraction of surplus value through the precarious working conditions (maquila regimes, outsourcing, migration, flexibility labor, etc.) and also, as I have already noted, the irrational extraction and appropriation of natural resources. Two phenomena are presented, as paradoxes of our time, on the one hand, the devaluation of human work, and on the other hand, the revaluation of materials raw and natural resources.